The Effect of Supervision and Quality of Work Life on Organizational Commitment in Moderation of Work Discipline in The Representative Office of Bank Indonesia, North Sumatera Province - Hidayat, M. Agus; Farida Ferine, Kiki (PT. Multidisciplinary Press Indonesia, 2024)
Human resources are essentially people who work for an organization as planners, thinkers and movers to achieve its goals. Human resources (HR) personnel are often highly skilled individuals who serve as the backbone of an organization. This research aims to examine the influence of supervision and quality of work life on organizational commitment in moderating work discipline at the Bank Indonesia Representative Office, North Sumatra Province. The results of this research are as follows: Work Discipline has a positive and significant effect on Organizational Commitment with an original sample value of 0.300 and an ap value of 0.028. Supervision has a negative and insignificant effect on organizational commitment, moderated by Work Discipline with an original sample value of -0.094 and ap value of 0.232. Quality of Work Life has a positive and insignificant effect on organizational commitment, moderated by Work Discipline with an original sample value of 0.141 and ap value of 0.148. Quality of Work Life has a positive and significant effect on Organizational Commitment with an original sample value of 0.278 and ap value of 0.033. Supervision has a positive and significant effect on Organizational Commitment with an original sample value of 0.344 and ap value of 0.018.